Perancangan UI/UX Aplikasi Kesehatan Mental “MindEase” Berbasis Mobile dengan Metode Design Thinking - Pande Komang Bhargo Anantha Yogiswara; I Gusti Ngurah Anom Cahyadi Putra (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
The rising global concern over mental health disorders necessitates accessible and quality mental health services. In Indonesia, where 6.1% of the population aged 15 and above experience such disorders, addressing the increasing prevalence becomes imperative. However, barriers like resource scarcity, limited geographic access, and social stigma hinder individuals from accessing professional help. More than 80% of affected individuals lack access to quality, affordable mental health services. In response, the mobile application "MindEase" emerges as an innovative solution, integrating consultation, assessment, education, and training in one platform. Designed to alleviate stress and anxiety, MindEase aims to provide users with a comfortable environment for managing their mental health. Aligned with the Sustainable Development Goals, particularly SDG #3 and #10, MindEase contributes to promoting better mental health and reducing healthcare disparities. Using the design thinking method, the UI/UX of MindEase was developed, resulting in satisfactory usability, as indicated by a System Usability Scale score of 82.8125. However, future research should involve mental health professionals for more comprehensive evaluations.